A personalized active learning plan for students within the framwwork of the Erasmus+ RE_EDUCO Project - Faka, Alexandra; Toumazi, Toumazis (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Within the framework of the Erasmus+ funded project RE-EDUCO - Rethinking Education Competencies. Expertise, best practices, and teaching in the Digital Era , the Intellectual Output 4 (IO4) required the development of a personalized active learning plan for students that catered for the assessment of the current level of the students participating in the project. The assessment aimed to identify their training needs in required digital skills to successfully develop a report for the description of their start-up company s idea and the presentation in front of a panel of judges in the context of a competition. In fact, the IO4 was created in close connection with the IO3, which involved the participating students of the entire consortium in a contest of ideas that developed first at a national level and then at an international level. The Cyprus Computer Society (CCS) was the consortium’s project partner responsible for the achievement of IO4. The sections below describe the process followed by the team of the CCS to bring to a successful completion this activity.